Sistema multiagente web semântico para gestão de conteúdos educacionais - Sandoval Romo, Bernarda Cecibel [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The use of the Web as a platform for distance education (e-learning), has been one of the great alternatives for education in traditional classrooms. Although these systems are widely used, there are limitations related to the difficulty of search, integration and reuse of learning objects (LOs). The integration of Semantic Web, ontologies and intelligent agents technologies in Web-based educational systems, improve the adaptation and interoperability processes of educational environments, especially in the recovery and recommendation of LOs. Ontologies are used for the integration and sharing of resources, while the intelligent agent technology is used for the development of autonomous, flexible and interactive components, allowing better management, control and integration of the involved activities. The objective of this work was to propose a multi-agent architecture to serve as a reference model for the development of Semantic Web systems for management of educational content. A literature review was conducted to define the main requirements of this architecture. Using an agent-oriented software development methodology a set of agents was identified and specified. The agents were defined in order to automate the activities related to management of educational content such as the authoring of LOs metadata and courses, search and semantic annotation of LOs. A set of ontologies was specified for the semantic annotation of LOs and courses, in order to describe the application knowledge and to integrate LOs described by heterogeneous metadata standards, retrieved from different repositories. The knowledge held in these ontologies assists teachers in the activities of authoring of LOs metadata, construction and update their courses. Using the proposed architecture a prototype was developed to annotate and integrate LOs of Mathematics discipline for ninth year of elementary school. The LOs used for tests...

A utilização da Web como plataforma para a educação a distância (e-learning) tem sido uma das grandes alternativas para a educação em sala de aula tradicional. Embora esses sistemas sejam amplamente utilizados, existem limitações quanto à dificuldade de busca, integração e reuso dos objetos de aprendizagem (OAs). A incorporação das tecnologias da Web Semântica, ontologias e agentes inteligentes nos sistemas educacionais baseados na Web, permitem aprimorar os processos de adaptação e de interoperabilidade dos ambientes educacionais, principalmente na recuperação e na recomendação de OAs. As ontologias são utilizadas para a integração e o compartilhamento de recursos, enquanto a tecnologia de agentes inteligentes é utilizada para o desenvolvimento de componentes autônomos, flexíveis e interativos, permitindo um melhor gerenciamento, controle e integração das atividades envolvidas. Assim, o objetivo deste trabalho foi propor uma arquitetura multiagente para servir como modelo de referência para o desenvolvimento de sistemas Web semânticos para a gestão de conteúdos educacionais. Um levantamento bibliográfico foi realizado para definir os principais requisitos desta arquitetura. Um conjunto de agentes foi identificado e especificado, utilizando uma metodologia de desenvolvimento de software orientada a agentes. Os agentes foram definidos para a automação das atividades relacionadas à gestão de conteúdos educacionais, tais como a autoria de metadados de OAs e de cursos, a busca e a anotação semântica de OAs. Um conjunto de ontologias foi especificado para a anotação semântica dos OAs e dos cursos, com o objetivo de descrever o conhecimento da aplicação e integrar OAs descritos por padrões de metadados heterogêneos, recuperados de diferentes repositórios. O conhecimento mantido nessas ontologias auxilia os professores nas atividades de autoria de metadados de OAs...
Keywords: Computação - Matemática; Web semântica; Ontologias (Recuperação da informação); Sistemas multiagentes; Objetos de aprendizagem; Computer science - Mathematics